2017
DOI: 10.1123/jpah.2016-0712
|View full text |Cite
|
Sign up to set email alerts
|

Do Sitting, Standing, or Treadmill Desks Impact Psychobiological Indicators of Work Productivity?

Abstract: The findings highlight the potential benefits of standing or active deskwork to the allocation of attentional resources and the regulation of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 15 publications
0
41
2
Order By: Relevance
“…It is well known that cortisol is released by the hypothalamic–pituitary–adrenal axis in response to stress [42], and it is a reliable indicator of endocrine stress responses [43]. Although it is uncertain why no differences in saliva cortisol were found between conditions here, a recent study found that doing deskwork while sitting throughout the slightly decreased saliva cortisol in comparison to doing nothing while sitting [44]. This may indicate that sitting per se cannot reduce psychological stress.…”
Section: Discussionmentioning
confidence: 87%
“…It is well known that cortisol is released by the hypothalamic–pituitary–adrenal axis in response to stress [42], and it is a reliable indicator of endocrine stress responses [43]. Although it is uncertain why no differences in saliva cortisol were found between conditions here, a recent study found that doing deskwork while sitting throughout the slightly decreased saliva cortisol in comparison to doing nothing while sitting [44]. This may indicate that sitting per se cannot reduce psychological stress.…”
Section: Discussionmentioning
confidence: 87%
“…Fourteen studies employed a cross-sectional design [28][29][30][31][32][33][34][35][36][37][38][39][40][41] (n=72-34,129 participants). Four studies were longitudinal [28,[42][43][44] (n=271-11,676), one was a controlled clinical trial [45] (n=43), two were pilot interventions [46,47] (n=12-20), and two were direct observation studies (i.e. where time in sedentary behaviour was collected for one year or one month and averaged) [28,48] (n=79-140).…”
Section: Resultsmentioning
confidence: 99%
“…Objective measures of stress were used in n=5 studies, and included salivary [32,[45][46][47] or hair [39] cortisol, blood pressure (systolic and diastolic) [45], and heart rate [45]. Stress was self-reported using measures including the Life Events Inventory (LEI, n=3) [28], the Cohen Perceived Stress Scale (PSS, n=7) [30, 33-35, 38, 42, 43], the Depression, Anxiety, and Stress Scale (DASS-21, n=1) [36], the Perceived Stress Questionnaire for Young Women (PSQYW, n=1) [44], the affective experience component of the Princeton Affect and Time Survey (n=1) [31], the Daily Stress Inventory (DSI, n=1) [48], the Chronic Burden Scale (CBS, n=1) [40], the Traumatic Stress Schedule (TSS, n=1) [40], job stressors (n=1) [37], and the Effort Reward Imbalance Scale (ERIS, n=1) [41].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 622 participants took part (229 males, 311 females, 82 unidentified). One study was a RCT [35], one study was of a non-randomized parallel group design [36] and 20 studies were CO in design [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Seven studies evaluated a cycling intervention, 13 studies evaluated a walking intervention and two studies evaluated both types of intervention (see Supplementary File 2).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Blood glucose levels were assessed by three studies [41,50,52] and insulin levels by two studies [41,52]. One study [46] assessed dopamine levels and two studies [46,56] assessed cortisol levels.…”
Section: The Effects Of Interventions On Cardiovascular Indicatorsmentioning
confidence: 99%